2012
DOI: 10.1001/archdermatol.2012.2974
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of Squamous Cell Carcinoma and Keratoacanthoma

Abstract: To characterize dermoscopic criteria of squamous cell carcinoma (SCC) and keratoacanthoma and to compare them with other lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
167
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(192 citation statements)
references
References 23 publications
17
167
1
7
Order By: Relevance
“…However, the presence of central keratin favours a diagnosis of keratoacanthoma over squamous cell carcinoma. This finding is crucial as it correlates to a central keratin plug on histopathology of keratoacanthoma [1].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the presence of central keratin favours a diagnosis of keratoacanthoma over squamous cell carcinoma. This finding is crucial as it correlates to a central keratin plug on histopathology of keratoacanthoma [1].…”
Section: Discussionmentioning
confidence: 87%
“…The white mass with central blood spots and keratin crusts along with the characteristic peripheral arrangement of hair pin blood vessels is diagnostic of keratoacanthoma [1]. Also, the peripheral arrangement of hair pin blood vessels favours a diagnosis of keratoacanthoma over seborrheic keratosis in which the hair pin vessels are evenly distributed throughout the lesion [2].…”
Section: Discussionmentioning
confidence: 99%
“…21,29 Yüksek riskli hastalarda önerilen tedavi yöntemi Mohs cerrahisidir. 21,30,31 Dermatoskopik inceleme, kötü diferansiye skuamöz hücreli karsinomların iyi ve orta diferansiye skuamözden ayrımını sağlayarak tedavi planlamasına yardımcı olabilir. 32 Son yıllarda yapılan çalışmalarda; ultrasonografi (USG), optik koherens tomografi, konfokal mikroskopi, pozitron emisyon tomografi gibi gö-rüntüleme yöntemlerinin NMCK tanısına katkısı araştırılmıştır.…”
Section: Bulgularunclassified
“…Keratin crust/scale had the highest sensitivity for keratoacanthoma and SCC (79%) and with circles had the highest specificity (87%). 25 Lin et al 26 have observed white circles in 32% of SCCs and 38% of keratoacanthomas, keratin crust/scale in 90% of SCCs and all of keratoacanthomas and central keratin masses in 32% of SCCs and 88% keratoacanthomas.…”
mentioning
confidence: 98%
“…It is characterized by rapid growth over a few weeks to months, followed by spontaneous resolution over 4-6 months in most cases, but rarely it may progress to invasive carcinoma. Rosendahl et al 25 identified several dermoscopic criteria that help differential keratoacanthoma from SCC and other nonpigmented lesions. The most important dermoscopic clues to keratoacanthoma and SCC are white circles, keratin crust/scale, blood spots, and white structurless zones.…”
mentioning
confidence: 99%